Replacement of Yellow Maize with Citrus Peels Fermented with Saccharomyces Cerevisiae on the Growth Performance and Biochemical Profile of Nile Tilapia - L. C. Nwanna; G. Oboh; G. Agbede; V. Atufe (Journal of Applied Sciences and Environmental Management)
The objective of this study was to investigate the effect of replacement of yellow maize with citrus peels fermented with Saccharomyces cerevisiae on the growth performance and biochemical profile of Nile tilapia using appropriate standardized procedures. Results showed that growth performance was the same (P > 0.05) in all the treatment groups. Fish weight gain, specific growth rate and feed conversion ratio followed the same trend. Fish weight gain was 10.8, 10.0, 9.86, 9.76 and 8,80g respectively in fish fed diets 1 -5. The peels significantly increased the carcass iron, and with marginal increments in other minerals. The effect of the peels reduced marginally the total cholesterol, malondialdehyde, glucose, triglyceride, low density lipoprotein; while the high-density lipoprotein increased marginally. In conclusion, Saccharomyces cerevisiae fermented citrus peels can replace 100% of yellow maize in the diets of Nile tilapia; and improve the nutritional qualities of the food fish.